2013
DOI: 10.1037/a0032044
|View full text |Cite
|
Sign up to set email alerts
|

Why do comparative assessments predict health? The role of self-assessed health in the formation of comparative health judgments.

Abstract: These data revealed that CH judgments were, to a great extent, based on SAH. Results showed that motivational factors influence CH judgments but do not explain the differences between SAH and CH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…Self-rated health is a major independent predictor of objective health, morbidity, and mortality [44, 45] and symptoms such as chronic pain and fatigue are particular important constituents of self-rated health. Additionally, chronic pain is independently and significantly related to self-rated health [46] while impaired general health is associated with poor recovery from chronic pain [47].…”
Section: Discussionmentioning
confidence: 99%
“…Self-rated health is a major independent predictor of objective health, morbidity, and mortality [44, 45] and symptoms such as chronic pain and fatigue are particular important constituents of self-rated health. Additionally, chronic pain is independently and significantly related to self-rated health [46] while impaired general health is associated with poor recovery from chronic pain [47].…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that procrastination as a trait is associated with a range of stress-related acute health problems such as headaches, digestive issues, colds and flus, and insomnia (Sirois, 2007a;Sirois, Melia-Gordon, & Pychyl, 2003;Sirois, Voth, & Pychyl, 2009). Procrastination is also linked to poor self-rated health (Sirois & Tosti, 2012), a reliable indicator and predictor of poor objective health and health-related outcomes such as cortisol responses to stress, morbidity, and mortality (Jylhä, 2009;Kristenson, Olsson, & Kucinskiene, 2005;Mora, Orsak, DiBonaventura, & Leventhal, 2013;Tamayo-Fonseca et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most research has focused on their association with mortality [1,2]. Several studies have concluded that CH is mediated through SRH [3,4] but have not explored or compared both SRH and CH in relation to other health indicators in large populations. In light of prior research, we hypothesized that SRH would be more strongly associated with a variety of health indicators than CH was.…”
Section: To the Editormentioning
confidence: 99%